2013
DOI: 10.1016/j.devcel.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonautonomous Movement of Chromosomes in Mitosis

Abstract: Kinetochores are the central force-generating machines that move chromosomes during cell division. It is generally assumed that kinetochores move in an autonomous manner. However, we reveal here that movements of neighboring sister-kinetochore pairs in metaphase are correlated in a distance-dependent manner. This correlation increases in the absence of kinetochore oscillations or stable end-on attachments. This suggests that periodic movements of bioriented chromosomes limit the correlated motion of nonsisters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 53 publications
11
54
0
Order By: Relevance
“…Similarly, a previous study has shown that neighboring kinetochore pairs oscillate in a correlated manner, which was explained by elastic linkages between k‐fibers 37. Our results support the existence of lateral connections between adjacent bundles consisting of bridging and k‐fibers.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, a previous study has shown that neighboring kinetochore pairs oscillate in a correlated manner, which was explained by elastic linkages between k‐fibers 37. Our results support the existence of lateral connections between adjacent bundles consisting of bridging and k‐fibers.…”
Section: Resultssupporting
confidence: 91%
“…Like that, it is possible that hKif15 would contribute to the control of microtubule plus-end dynamics at the kinetochore; in this regard hKif15 has also been reported to localize to kinetochores (11) and influence chromosome movement (21). Promoting microtubule growth in the kinetochore fiber can indirectly create outwardpushing forces on the centrosome to assist spindle elongation.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, hKif15 is largely localized to parallel microtubule bundles (11,21). Thus, it might be possible that hKif15 uses geometry-dependent transport and (biased) parallel sliding to autonomously drive formation of parallel bundles.…”
Section: Kif15 Motors Can Only Translocate On Two Microtubules Simultmentioning
confidence: 99%
“…KIF23 was recently found to be the gene mutated in families with CDA type III. 9,54 Thus, there is a direct genetic link between KLF1 and CDA types IV and III. There are other novel KLF1 target genes that may be important for regulating mitosis including TRIB3, which controls cell division in response to erythropoietin.…”
Section: Klf1 Regulates the Cell Cycle And Mitosismentioning
confidence: 99%